Multi-species pattern analysis of Mediterranean pastures in three stages of ecological succession - Castro, Isabel; Sterling, Agustina; Galiano, E F (Plant Ecology, 1986)
Multi-species patterns were analyzed in three stages of ecological succession in oligotrophic pastures in Central Spain using a new method of analysis. The method is based on plotting the species coordinates of principal components analysis undertaken at different block sizes. It allows the detection of any heterogenei- ty present and reveals both microtopographical and macrotopographical trends in species patterns.
Keywords: grassland; mediterranean pasture; pattern analysis; principal components analysis; succession